Feasibility Analysis of Investment Facilities Of Slip Fish Processing Factory, Sorong District - Sri Sundari (Journal Research of Social Science, Economics, and Management, 2022)
The potential of marine resources in Sorong Regency, West Papua is very abundant, especially in the fisheries sector. The abundant potential of tuna makes it an attractive commodity. Fishery products are foodstuffs that are susceptible to post-catching spoilage so that they can last a long time, a canning process is needed. This study aims to analyze income, costs and investment decisions at a fish canning factory in Sorong Regency to obtain the feasibility of a project with quantitative research methods, because this study seeks to determine the value of the feasibility indicators of an investment project. The result of the investment criteria is an NPV of Rp. 7,841,604,054.00 is greater than zero, the IRR value is 97.84% greater than the 14% interest rate and the Net B/C value is 2.44 greater than one. The payback period is achieved within 2 years 7 months 6 days, meaning this business can cover the initial investment costs before the end of the business life. The sensitivity analysis carried out shows that the canned fish canning factory is feasible to run as long as the project runs according to the assumptions and technical parameters specified.